Effect of culture media and serum supplementation on the development of in vitro fertilized burno embryos - Kumar, D; Palta, P; Manik, R S; Singla, S K; Chauhan, M S (The Indian Journal of Animal Sciences, 2007)
This study was taken up to compare the development of buffalo embryos in simple and complex culture media and to determine the effects of serum supplementation of the simple media on the development of buffalo embryos. Usable quality buffalo oocytes were subjected to in vitro maturation in TCM-199+10% foetal bovine serum (FBS)+5 Âµg/ml porcine FSH+0.81 mM sodium pyruvate+5% buffalo follicular fluid for 24 h in a CO2 incubator (5% CO2 in air) at 38.5 degree Celcius. Oocytes which exhibited cumulus expansion were subjected to in vitro fertilization. After 18 h of sperm-oocyte incubation, the presumptive zygotes were divided randomly into 5 groups and cultured in one of the following 5 media-group 1: Control (TCM-199+10%FBS+co-culture with buffalo ,oviductal epithelial cells (BOEC); group 2: mCR2aa; group 3: mCR2aa+1O% FBS; group 4: mSOFaa and group 5: mSOFaa+lO% FBS. For each group, the medium was changed at 48 h post-insemination and then every 48 h till day 8 post-insemination. For groups 3 and 5, the oocytes were cultured in the absence of FBS till 48 h post-insemination. On day 8, the proportion of cleaved oocytes that developed to the morula + blastocyst stages was significantly higher for mSOFaa and mSOFaa+FBS (62.3 and 61.5%, respectively) than that of mCR2aa and mCR2aa+FBS (54.2 and 58.6%, respectively) which in turn, was significantly higher when compared with TCM-199+FBS+BOEC (48.6%). The proportion of cleaved embryos that developed to the blastocyst stage on day 9 was significantly higher for mSOFaa, mSOFaa+FBS and mCR2aa+FBS (42.0, 41.5 and 48.3%, respectively) when compared with mCR2aa (32.2%) which in turn, was significantly higher than that of TCM- 199+FBS+BOEC (14.3%). Higher yields of day-8 morulae and blastocysts or day-9 blastocysts were obtained with mCR2aa and mSOFaa, even without serum supplementation and co-culture with somatic cells than those obtained when a complex medium is used with somatic cell support and serum supplementation. Among the different media compared, mSOFaa was the most effective medium for supporting the development of buffalo zygotes to the morula and blastocyst stages.